Cast away - Zemeckis, Robert; Starkey, Steve; Zemeckis, Robert ([Beverly Hills, CA : 20th Century Fox Home Entertainment, 2001)
Chuck Noland, a FedEx systems engineer, finds his ruled-by-the-clock existence ended when a harrowing plane crash leaves him isolated on a remote island. As Chuck struggles to survive, he finds that his own personal journey has only just begun
Writer, William Broylee, Jr. ; executive producer, Jon Bradshaw
Cast: Tom Hanks, Helen Hunt, Nick Searcy
Keywords: Adventure films